Scala guide for data science professionals : Scala will be a valuable tool to have on hand during your data science journey for everything from data cleaning to cutting-edge machine learning : a course in three modules.: guide for data science professionals : Scala will be a valuable tool to have on hand during your data science journey for everything from data cleaning to cutting-edge machine learning : a course in three modules. (2017) - Unknown
No abstract available